Understanding microstructure of the brain by comparison of neurite orientation dispersion and density imaging (NODDI) with transparent mouse brain. (April 2017) - Sato, Kanako; Kerever, Aurelien; Kamagata, Koji; Tsuruta, Kohei; Irie, Ryusuke; Tagawa, Kazuhiko; Okazawa, Hitoshi; Arikawa-Hirasawa, Eri; Nitta, Nobuhiro; Aoki, Ichio; Aoki, Shigeki
Background: Neurite orientation dispersion and density imaging (NODDI) is a diffusion magnetic resonance imaging (MRI) technique with the potential to visualize the microstructure of the brain. Revolutionary histological methods to render the mouse brain transparent have recently been developed, but verification of NODDI by these methods has not been reported. Purpose: To confirm the concordance of NODDI with histology in terms of density and orientation dispersion of neurites of the brain. Material and Methods: Whole brain diffusion MRI of a thy-1 yellow fluorescent protein mouse was acquired with a 7-T MRI scanner, after which transparent brain sections were created from the same mouse. NODDI parameters calculated from the MR images, including the intracellular volume fraction (Vic) and the orientation dispersion index (ODI), were compared with histological findings. Neurite density, Vic, and ODI were compared between areas of the anterior commissure and the hippocampus containing crossing fibers (crossing areas) and parallel fibers (parallel areas), and the correlation between fiber density and Vic was assessed. Results: The ODI was significantly higher in the crossing area compared to the parallel area in both the anterior commissure and the hippocampus ( P  = 0.0247, P  = 0.00022, respectively). Neurite density showed a similar tendency, but was significantly different only in the hippocampus ( P  = 7.91E−07). There was no significant correlation between neurite density and Vic. Conclusion: NODDI was verified by histology for quantification of the orientation dispersion of neurites. These results indicate that the ODI is a suitable index for understanding the microstructure of the brain in vivo .